Among adolescents, addiction susceptibility and sleep-related dysfunction have a common cognitive-emotional base and predict poor sleep quantity. (4th July 2019) - Khazaie, Habibolah; Behrouz, Behrouz; Chehri, Azita; Gerber, Markus; Holsboer-Trachsler, Edith; Sadeghi Bahmani, Dena; Brand, Serge
ABSTRACT: Background: Among adolescents, the self-pacing of sleep and experimentation with psychotropic substances increases. Poor sleep and susceptibility to addiction (SA) may therefore share common cognitive-emotional processes. The aim of the present study was to investigate the shared cognitive-emotional basis of SA and sleep-related dysfunction, and to explore their predictive value for sleep patterns. Methods: A total of 300 adolescents (mean age: 15.57 years; 50% females) took part in this questionnaire-based study. Participants completed a booklet covering sociodemographic, sleep-related (Sleep Hygiene Index: SHI; Pittsburgh Sleep Quality Index: PSQI) and SA-related variables. Results: Greater sleep-related dysfunction based on the SHI was strongly associated with higher SA scores. Parents' educational level was negatively associated with SHI and SA scores. An exploratory factor analysis of SHI and SA items yielded three distinct factors: (i) risky behavior and irregular sleep-wake schedules, (ii) poor sleep environment and hygiene, and (iii) psychological arousal and distress. All three factors independently contributed to the prediction of poor sleep quality and quantity. Conclusions: Adolescents reporting dysfunctional cognitive-emotional processes are at increased risk of reporting poor sleep patterns. Additionally, poor sleep and SA were related to parents' education, suggesting that both parents and their children might benefit from sleep hygiene counseling.